Differentiation as a Form of Knowledge Production in Architecture - Benke, Brad; Christenson, Mike (ARCC Conference Repository, 2013)
Architectural models and photographs, foreground some perceptual aspects of architecture while minimizing the presence of others (Bermudez & King, 2000; Boge & Sullivan, 2006). Photographs highlight the value of a point of view, framing, and cropping. Digital models also embody points of view, as well as less obvious attributes such as the sequential order of construction (which may or may not correlateto the order of construction of the building being modeled).Using Villa Savoye as a test case, we examined the degree of differentiation between online models, and how these differences can be mapped and extrapolated to illuminate conditions potentially suggestive ofarchitectural significance in themselves – independent of any consideration of the models’ verisimilitude. We then asked: Are there limits to how "wrong” a model can be and yet still be capable of provoking significant insight? In reflecting on our processes, we questioned how the tools we have developed may facilitate forms of knowledge production historically essential to architectural epistemology but often overlooked in a contemporary discourse dominated by hyperaccurate models, predictive simulations, and photorealistic renderings. Our questions are aimed at making visible that which is essential to a critical architecture in which processesand tools generate and sustain a non-destructive environment for architectural research.